The Capacity of Coastal Gravel Beaches in Absorbing the Storm Wave Energy - Türker, Umut; Kabdaşli, M. Sedat (Springer Science and Business Media Deutschland GmbH, 2024)
Four series of laboratory experiments were conducted to observe the effect of storm waves on the morphologic changes of coastal bed profile. The aim was to interpret the relationship between the offshore bar and foreshore erosion profiles under the effect of storm waves and calculate the damage generated over the bed profile by the storm waves. The beach material was one of the most important factors on the short-term morphological changes of cross-shore bed profile, and the size of the bed material was composed of gravel. The relationship between the wave characteristics and post-storm bed profiles at different gravel sizes were analyzed and dimensionless parameters representing the event were discussed. Depending on the size of the gravels, the damage level over the profile exhibit variations where the damage level was characterized by the length measured in between the center of masses of offshore bar and foreshore erosion. Dimensionless parameters like damage parameter, resistance parameter and steepness parameter were effective in defining the damage. It was observed that the damage of coastal region increases as the beach profile gradient increases and the effective static stability was reached by increasing the size of the gravel particles or increasing the magnitude of dimensionless shore resistance parameter. © The Author(s), under exclusive license to Springer Nature Singapore Pte Ltd. 2024.
15th International Congress on Advances in Civil Engineering, ACE 2023 -- 2023-09-06 through 2023-09-08 -- Famagusta -- 312069
Keywords: Coastal Profile; Damage parameter; Dynamic Stability; Gravel; Wave Height